Teachers’ perspectives on using play-based learning for inclusive early childhood education classrooms - Mohoebi, Matšeliso Alice; Mokala, Ntsoaki Teresa (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Early Childhood Education (ECE) has grown significantly over the years. It has been prioritized as one of the Sustainable Development Goals (SDGs) of the United Nations under inclusive education. Under Sustainable Development Goals, goal 4 outlines inclusive, equitable, and quality education with lifelong learning opportunities for all. To ensure that inclusive education is achieved in Early Childhood Education programmes, teachers need to have the right skills necessary for teaching and supporting learners with neurodiversity. This qualitative study is lensed under interpretivism paradigm and framed theoretically by the Play-based Learning curriculum to understand teachers’ perspectives on the use of play-based learning for Early Childhood Education inclusive classrooms. The study was conducted in one Early Childhood Education centre for learners with neurodiversity in Botha-Bothe, Lesotho, where six teachers were purposively selected to take part in the study. Data was generated through face-to-face interviews guided by an interview schedule. To analyse data, thematic analysis was relevant for this study to unpack the experiences and perspectives of teachers across a data set. The findings revealed that teachers advocate for the use of play-based inclusive pedagogies to teach learners with neurodiversity; they understand the importance of using appropriate teaching methods which address learners’ needs and believe in their ability to teach and support the learners. Some of the challenges highlighted by the findings of the study point to lack of parental involvement and in-service training for teachers. The study concludes that further research is required to understand the gaps in teacher training and the support they need to fully support learners with neurodiversity.
Journal article published in the African Perspectives of Research in Teaching and Learning Journal Volume 10, Issue 1, 2026
Keywords: Early childhood education; Equity in education; Inclusive education; Playbased learning; Neurodiversity; Early childhood education; Education equalization; Mainstreaming in education; Education, Preschool; People with disabilities -- Education; Play